2017
DOI: 10.1111/iju.13470
|View full text |Cite
|
Sign up to set email alerts
|

Influence of dutasteride treatment on serum hormone levels and aging male symptoms in patients with benign prostatic enlargement

Abstract: Objectives: To clarify the effects of dutasteride on serum hormone levels and aging male symptoms in patients with benign prostatic enlargement. Methods: The present prospective study was carried out in 110 symptomatic benign prostatic enlargement patients treated with daily administration of 0.5 mg dutasteride. We analyzed serum hormonal levels and aging related symptoms using a validated Aging Male Symptom questionnaire at baseline and after 3 months of dutasteride treatment. Results: The mean total testoste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The present study is the first to show the potential beneficial effect of dutasteride in moderate LOH symptoms of patients with low baseline testosterone levels . A few recent studies have demonstrated that an increase in serum testosterone level by dutasteride administration shows certain beneficial effects in androgen‐responsive functions, including increased bone mineral density and decreased body mass index, particularly in men with low baseline testosterone levels .…”
mentioning
confidence: 54%
“…The present study is the first to show the potential beneficial effect of dutasteride in moderate LOH symptoms of patients with low baseline testosterone levels . A few recent studies have demonstrated that an increase in serum testosterone level by dutasteride administration shows certain beneficial effects in androgen‐responsive functions, including increased bone mineral density and decreased body mass index, particularly in men with low baseline testosterone levels .…”
mentioning
confidence: 54%
“…Serum total or free testosterone levels below the lower limit of normal levels would affect sexual function. 31 In addition, though medication compliance was stipulated to be over 90%, numbers and data about compliance and drug count were not available. Third, we did not assess the relationship between risk factors of ED such as smoking/diabetes and the effect of dutasteride.…”
Section: Discussionmentioning
confidence: 99%
“…found the changes in the rate of luteinising hormone (LH) after three months of dutasteride treatment for 110 BPH patients tended to correlate with an increase in the rate of total T and free T after dutasteride treatment. 20 However, Clark et al. observed little or no significant increases in LH serum concentration after a 24 week finasteride or dutasteride treatment compared to placebo, 4 and they suggested selective inhibition of type 2 5α-reductase in men has little effect on serum gonadotropin levels or on the LH response to gonadotropin releasing hormone.…”
Section: Discussionmentioning
confidence: 99%